Simulated stability of the Atlantic Meridional Overturning Circulation during the Last Glacial Maximum - F. Pöppelmeier; J. Scheen; A. Jeltsch-Thömmes; T. F. Stocker (Climate of the Past, 2021)
The response of the Atlantic Meridional Overturning Circulation (AMOC) to freshwater perturbations critically depends on its mean state. Large swaths of icebergs melting in the North Atlantic during the last deglaciation constituted such perturbations and can, thus, provide important constraints on the stability of the AMOC. However, the mean AMOC state during the Last Glacial Maximum (LGM), preceding the rapid disintegration of the ice sheets during the deglaciation, as well as its response to these perturbations remain debated. Here, we investigate the evolution of the AMOC as it responds to freshwater perturbations under improved LGM boundary conditions in the Bern3D intermediate complexity model. Particularly, we consider the effect of an open versus a closed Bering Strait and the effect of increased tidal dissipation as a result of the altered bathymetry due to the lower glacial sea level stand. The vigorous and deep AMOC under these glacial boundary conditions, consistent with previous simulations with different models, reacts more strongly to North Atlantic freshwater forcings than under preindustrial conditions. This increased sensitivity is mostly related to the closed Bering Strait that cuts off the freshwater escape route through the Arctic into the Pacific, thereby facilitating faster accumulation of freshwater in the North Atlantic and halting deep-water formation. Proxy reconstructions of the LGM AMOC instead indicate a weaker and possibly shallower AMOC than today, which is in conflict with the particularly strong and deep circulation states coherently simulated with ocean circulation models for the LGM. Simulations with reduced North Atlantic deep-water formation, as a consequence of potentially increased continental runoff from ice sheet melt and imposed changes in the hydrological cycle, more closely resemble the overturning circulation inferred from proxies. These circulation states also show bistable behavior, where the AMOC does not recover after North Atlantic freshwater hosing. However, no ...